Troponin Elevation after Noncardiac Surgery: Significance and Management at JPMC Karachi - IRFAN ALI; ZAHID MEHMOOD; KANWAL SOOMRO; FALAK NAZ; SHAMSHER ABBAS MEMON; TARIQ HUSSAIN (Pakistan Journal of Medical & Health Sciences, 2025)
Aim: To evaluate the incidence and prognostic significance of Troponin I for cardiac risk in patients undergoing noncardiac surgery at Jinnah Postgraduate Medical Centre (JPMC), Karachi. Study Design: A quantitative, cross-sectional study. Place and duration of study: General Surgical Ward 3 at JPMC Karachi over eight months from February to October 2024. Methodology: We examined 927 patients who underwent noncardiac surgery. Data on patient demographics, medical histories, type of surgery, and postoperative Troponin I levels were collected and analyzed using descriptive statistics, chisquare tests, and regression analysis in SPSS. Results: Troponin I levels were significantly elevated in 52 cases (5.6%), demonstrating a statistically significant relationship with the diagnosis and postoperative day, and a marginally significant relationship with comorbidities. Conclusion: Increased Troponin I levels were found in a significant number of patients post-noncardiac surgery, potentially indicating the early stages of developing cardiac complications. Regular monitoring of Troponin I levels in postoperative patients is recommended to facilitate early identification and management of additional complications. Keywords: Troponin I, noncardiac surgery, postoperative outcomes, cardiac complications, JPMC